ANALYZING INFLUENCE OF MUSIC IN DEVELOPING LANGUAGE YOUNG LEARNEERS - Assadilah, Agung; Barokah, Nurahman (IKIP Siliwangi, 2018)
The purpose of this study to determine the effect of music in language learning against young students in one primary school in Batujajar Kabupaten Bandung Barat. Some of the things that become the focus in this research is how much influence created from music when applied in language learning especially for young learners. This study uses case study design. The subject of this research is the some students of first grade of elementary school. Subjects were analyzed based on their abilities after the application of this study and any positive impact that arose from young learners after the study. And reported descriptively. After analyzed the data shows the influence of music, that students look more excited in the process of learning the language. The data also indicated that some students be able to showed cheerfulness and showed good interaction with the other students. With reference to the findings suggested to teachers to teach the language especially to young learners can use the music as a support in the teaching process.Key words:Music, Language, Young Learner.